‘Safety Matters Have Become Too Important for Management to Leave it Up to the Workers’ –The Nordic OSH Model Between Implicit and Explicit Frameworks - Dyreborg, Johnny (Nordic Journal of Working Life Studies, 2011)
In a globalized economy it is relevant to question whether the Nordic Working Environment (WE) model will remain as the basic and implicit framework for the governance of the WE. This paper explores institutional changes in the governance of the WE, and critically examines how a more explicit and market-oriented framework might influence the governance of the WE in the Nordic countries. Firstly, the paper examines the changes in the governance of the WE at the societal level (Denmark) for the period 1954 - 2007, and identifies institutional logics informing these changes. Secondly, the paper examines changes in the governance of the WE at the level of the construction sector, using case material from four of the largest construction projects completed in Denmark in recent years. The analyses reveal three discrete periods, representing distinct logics influencing the governance of the WE, i.e., the logic of the state, the logic of democracy and the logic of the market. The logic of the state and the logic of democracy represent an implicit framework, whereas the logic of the market entails a shift to a more explicit framework. The shift to a more explicit framework for the governance of the WE, is also identified at the level of the construction sector. This leads to a pivotal shift in the clients’ and the construction companies’ relationship with the institutional environment in the four large construction projects. From worker representatives being the primary stakeholders, to a shift where the fulcrum of the development of the WE lies between management, the state and stakeholders in the companies’ environment. This shift opens up a range of new and more market-oriented approaches to the governance of the WE that seems to challenge the extant Nordic WE model.